Prevalence of Dental Number Anomalies Among A Group of Turkish Children - Topal Burcu Güçyetmez (Sciendo, 2021)
Background/Aim: The study aimed to evaluate the prevalence and distribution of congenital dental number anomalies in the permanent dentition among a group of Turkish children in the Inner Aegean Region of Turkey.